Begonia caryotarum (Begonia sect. Platycentrum), a new species from southeast Yunnan, China - Dong, Wen-Ke; Li, Jing-Xiu; Chen, Wen-Hong; Xiao, Bo; Shui, Yu-Min (Phytotaxa, 2021)
We describe Begonia caryotarum (B. sect. Platycentrum), a new species from southeast Yunnan, China, found in rock crevices at the foot of limestone hills in Caryota obtusa forest at elev. 700–900 m. The new species is most similar to B. hekouensis in having the same vestiture type on the petioles, flower tepal number, placentation structure, and ovary shape and color, but differs mainly in its leaf blade being asymmetric with an acute apex, tepals pinkish- to orangish-red, larger staminate tepals, anther connectives slightly extended, stigma once spiraled. Its conservation status is categorized as Critically Endangered [CR B2ab (ii, iv), C2a(i)].